THE MEANING OF “PENANDAI” IN NOVEL OF SANG PENANDAI BY TERE LIYE: A SEMANTIC STUDY - Safrizal, . (PEOPLE: International Journal of Social Sciences, 2017)
This study aimed to investigate the collocation meaning of the word “penandai”. This reseacrh focused on the word “penandai”. Data obtained from the novel “Sang Penandai” created by Tere Liye (2016). The method, researcher using technique of analysis collocation. The collocation obtained by using a tool, that is, AntConc v 3.4.4. The results of this study showed that: (1) the word "penandai" raises the frequency with the word, Jim, dongeng ‘fairy tale’, remiez, rhenal. Based on the word that is collocated, founded the meaning of the word "penandai" is (1) something (someone) are glorified, (2) helper, and (3) the maker (fairy tale).